2012
DOI: 10.1123/ijsc.5.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Six Degrees of Information: Using Social Network Analysis to Explore the Spread of Information Within Sport Social Networks

Abstract: Sport industry groups including athletes, teams, and leagues use Twitter to share information about and promote their products. The purpose of this study was to explore how sporting event organizers and influential Twitter users spread information through the online social network. The study examined two bicycle race organizers using Twitter to promote their events. Using social network analysis, the study categorized Twitter messages posted by the race organizers, identified their Twitter followers and shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 11 publications
3
63
0
5
Order By: Relevance
“…Sports stadiums can make fans more aware of social media while at live events by posting messages on scoreboards, the field of play, websites and game programs (Delia & Armstrong, 2015). Other ways sports stadium professionals might increase awareness of sports stadium social media efforts include announcements made during the game, advertising, and promotions (Pronschinke et al, 2012), and by encouraging owners, coaches and star players to post user-generated content on Twitter and Facebook about sports stadiums (Hambrick, 2012); social media has also been shown to enhance the positive word-of-mouth that attendees at venues share about other events such as concerts and festivals (Hudson, Hudson, Roth, & Madden, 2015). The MetLife Stadiumuses an interesting approachin which fans are made aware of the stadium's social media program through posters and signs throughout the venue and messages displayed on the giant score board.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sports stadiums can make fans more aware of social media while at live events by posting messages on scoreboards, the field of play, websites and game programs (Delia & Armstrong, 2015). Other ways sports stadium professionals might increase awareness of sports stadium social media efforts include announcements made during the game, advertising, and promotions (Pronschinke et al, 2012), and by encouraging owners, coaches and star players to post user-generated content on Twitter and Facebook about sports stadiums (Hambrick, 2012); social media has also been shown to enhance the positive word-of-mouth that attendees at venues share about other events such as concerts and festivals (Hudson, Hudson, Roth, & Madden, 2015). The MetLife Stadiumuses an interesting approachin which fans are made aware of the stadium's social media program through posters and signs throughout the venue and messages displayed on the giant score board.…”
Section: Discussionmentioning
confidence: 99%
“…Many fans are using social media at venues before, during and after sports events (Ball, 2015), and are creating user-generated social media content (Stavros, 2013). As a result, the increased use of social media by spectators at sports venues is creating greater awareness and buzz for the stadium, the teams that play there, the sites that host sports competitions, and the events that take place at these sites (Hambrick, 2012;Vorvoreanu, Boisvenue, Wojtalewicz, & Dietz, 2013). Several studies point out how greater numbers of fans are sharing information on social networks while watching sports events on television and other media platforms (Lim, Young, Kim, & Biocca, 2015;Master, 2015) thus it seems likely that fans will also want to share on social media while at live sports events.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of social networks for contact with athletes and sports organizations through using the example of Twitter has been tested several times in the United States . Recently, social network analysis revealed relationships between sports journalists and athletes during certain periods around sporting events and identified clearly perceptible networks (Hambrick, 2012;Hambrick and Sanderson, 2013)…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theoretically existing studies found that promoting the spreading dynamics could induce distinct critical phenomena with different outbreak thresholds and critical exponents [8]. Practically speaking, promoting the spreading dynamics could shed some lights on the propagation of information [9][10][11], marketing management [12,13], disease spreading [14][15][16][17][18], etc. Many strategies for promoting spreading dynamics have been proposed, such as choosing influential seeds [19,20] and designing effective contact strategies [21,22].…”
Section: Introductionmentioning
confidence: 99%